A comparison of the performance of fully versus partially encapsulated cable bolts based on laboratory-scale testing - B Loh; P Hagan; D Li; S Wang (The Australasian Institute of Mining and Metallurgy, 2018)
A study was undertaken to quantify the differences in performance between a full-length encapsulated cable bolt and a partially encapsulated cable bolt. Much research has been reported on the differences in cable bolt design and operational parameters such as borehole diameter and grout type with much of this based on the Laboratory Short Encapsulation Pull Test (LSEPT). However, there is a gap in knowledge surrounding the effect of anchorage length on load transfer and cable bolt performance particularly with respect to the role of the bulb in modified cable bolt designs. The objective of this study was to expand the existing knowledge base of cable bolt performance with the intent of developing a revised design criterion. Alongside a comprehensive review of current cable support theory, design and practice, a series of pull tests was undertaken to compare each anchorage method using a high capacity modified cable bolt. The results serve to confirm earlier work on fully encapsulated anchorage. Both the peak load capacity and stiffness of the fully encapsulated cable bolt were nearly double that of the partially anchored cable bolt. When the tests were repeated in an oversized borehole, while there tended to be more variation in performance, there was little significant difference in the mean results. In addition to anchorage length, there are other factors that contribute to cable bolt performance including in order of sensitivity: embedment length, water-to-cement ratio of the grout, type of grout and borehole diameter. CITATION:Loh, B, Hagan, P, Li, D and Wang, S, 2018. A comparison of the performance of fully versus partially encapsulated cable bolts based on laboratory-scale testing, in Proceedings The Fourth Australasian Ground Control in Mining Conference (AusRock), pp 291–302 (The Australasian Institute of Mining and Metallurgy: Melbourne).